Acute aortic dissection as a late and fatal complication of transcatheter persistent ductus arteriosus occlusion: a case report. Issue 1 (11th December 2020) - Baker, David W; Celermajer, David S
Abstract: Background : Persistent ductus arteriosus (PDA) is a common congenital heart defect, of which, the preferred treatment in children and adults is transcatheter occlusion. This report describes the first reported case of acute aortic dissection as a late complication of transcatheter PDA occlusion. Case summary : A 66-year-old healthy woman, with a history of transcatheter PDA closure 12 years previously, died suddenly at home. Post-mortem revealed pericardial tamponade complicating an acute aortic dissection, with a large intimal tear identified adjacent to the PDA occluder. Discussion : Transcatheter occlusion is accepted as a safe and effective treatment in older children and adults, important in preventing haemodynamic sequelae such as heart failure and pulmonary hypertension. Complications are uncommon and mostly acute, including device embolization and haemolysis. Aortic dissection has been reported as an acute complication but only in the setting of incorrect device deployment. This is the first description of aortic dissection as a late complication of transcatheter PDA occlusion and although rare has important ramifications given it is a potentially fatal outcome of a common procedure.